Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd006577.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Music for stress and anxiety reduction in coronary heart disease patients

Abstract: Music listening may have a beneficial effect on blood pressure, heart rate, respiratory rate, anxiety, and pain in persons with CHD. However, the quality of the evidence is not strong and the clinical significance unclear.Most studies examined the effects of listening to pre-recorded music. More research is needed on the effects of music offered by a trained music therapist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
163
0
18

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(191 citation statements)
references
References 32 publications
10
163
0
18
Order By: Relevance
“…Araştırmamıza benzer şekilde Bal'ın (2002) araştırmasında da, bireylerin işlem öncesi anksiyete puan ortalamalarına bakıldığında, yüksekokul ve üniversite mezunlarının düşük anksiyeteye sahip oldukları görülmüş ancak eğitim düzeyine göre istatistiki açıdan anlamlı bir fark bulunmamıştır. [20] Bireysel özellikleri ne olursa olsun, bireyin kendisini tehdit eden herhangi bir durum karşısında anksiyete yaşadığı, [9,17] dolayısıyla hemşirelerin girişim ünitesine gelen tüm hastaların anksiyetesini belirleyip, gerekli hemşirelik yaklaşımını göstermeleri gerektiği söylenebilir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Araştırmamıza benzer şekilde Bal'ın (2002) araştırmasında da, bireylerin işlem öncesi anksiyete puan ortalamalarına bakıldığında, yüksekokul ve üniversite mezunlarının düşük anksiyeteye sahip oldukları görülmüş ancak eğitim düzeyine göre istatistiki açıdan anlamlı bir fark bulunmamıştır. [20] Bireysel özellikleri ne olursa olsun, bireyin kendisini tehdit eden herhangi bir durum karşısında anksiyete yaşadığı, [9,17] dolayısıyla hemşirelerin girişim ünitesine gelen tüm hastaların anksiyetesini belirleyip, gerekli hemşirelik yaklaşımını göstermeleri gerektiği söylenebilir.…”
Section: Discussionunclassified
“…[6,7] Yapılan araştırmalarda hemşire-lerin anjiyografi uygulamasında bireylerin; duygusal olarak rahatlamalarını sağlama, KAG ve PTKA işleminin tüm aşa-malarında yanlarında olarak işlemle ilgili bilgilendirme, gevşeme ve solunum egzersizleri yaptırma, müzik dinletme gibi yöntemlerle bireylerin anksiyete düzeylerini azaltabilecekleri vurgulanmıştır. [4,8,9] Sağlık bakım profesyonelleri hastanın anksiyetesinin nedenlerini ve düzeyini belirlemeye çalışmalı, hastanın anksiyetesinin azaltılması için neler yapılabileceğini tanımlama-lıdırlar. Bunun için; fiziksel/tıbbi hastalığı ya da yakınması nedeniyle hastaneye başvuran hastaların ve ailelerinin sağ-lığını geliştiren, primer korumadan rehabilitasyona kadar uzanan yelpazede ortaya çıkan bilişsel, psikolojik, davranışsal tepkilerini ve psikososyal sorunlarını tanımlayan konsültas-yon liyezon psikiyatri hemşirelerine (KLPH) ihtiyaç vardır.…”
Section: Introductionunclassified
“…Several studies indicate a connection between singing as a means of self-expression, regulation of emotions, and health and well-being [5759]. Moreover, the availability of psychobiological methodology over the last decades such as the ambulatory assessment of humoral stress markers or functional imaging have confirmed that the experienced stress releasing effects of music have indeed a psychophysiological bases [60,61].…”
Section: Singing Emotion Regulation and Well-beingmentioning
confidence: 99%
“…Such beliefs pervade most ancient cultures and recently a physiological basis for these beliefs has been posited. Studies now indicate that specific music has a positive effect on cardio-respiratory function, including: a reduction in blood pressure: a stabilisation of heart and respiratory rates: and an increase in oxygen saturation (Bradt and Dileo, 2009;Trappe, 2009). Nonetheless, although the therapeutic and soothing properties of music are well recognised, and there is mounting evidence of measurable physiological benefits, the mechanisms by which changes occur are not fully understood.…”
Section: Introductionmentioning
confidence: 99%